Об идентичности Aedes (Ochlerotatus) simanini Gutsevich и Ае. (О.) niphadopsis Dyar et Knab (Diptera, Culicidae) - Данилов, В.Н. (Вестник зоологии, 1981)
The arguments are given to confirm the opinion that the name Aedes (Ochlerota- lus) simanini Gutsevich , 1966 for mosquitoes from Middle Asia and Kazakhstan (USSR) is a synonym of Ae.(Och.) niphadopsis. Dyar e tKnab, 1918 for mosqui- toes from North America (USA and Canada). Thus, Ae. niphadopsis. (=Ae. simanini) is a species having a broken disfunctive Molarctic range a map of its geographical distribution is given. some divergences in the descriptions or Ae. mphadopsis and Ae. simanint are discussed and explained.